2017
DOI: 10.1002/ece3.2889
|View full text |Cite
|
Sign up to set email alerts
|

Temperature increase and fluctuation induce phytoplankton biodiversity loss – Evidence from a multi‐seasonal mesocosm experiment

Abstract: Global climate change scenarios predict lake water temperatures to increase up to 4°C and extreme weather events, including heat waves and large temperature fluctuations, to occur more frequently. Such changes may result in a reorganization of the plankton community structure, causing shifts in diversity and structure toward a community dominated by fewer species that are more adapted to endure warmer and irregular temperature conditions. We designed a long‐term (8 months) mesocosm experiment to explore how am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
67
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(82 citation statements)
references
References 50 publications
14
67
1
Order By: Relevance
“…In accordance with our findings, Rasconi et al. () reported that long‐term temperature increases as well as temperature fluctuations significantly decreased phytoplankton SDiv (inferred from the number of genera) in a mesocosm study. Similarly, in their microcosm experiment with benthic microalgae, Eggers, Eriksson, & Matthiessen, demonstrated that Shannon diversity significantly declined after a heat wave.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In accordance with our findings, Rasconi et al. () reported that long‐term temperature increases as well as temperature fluctuations significantly decreased phytoplankton SDiv (inferred from the number of genera) in a mesocosm study. Similarly, in their microcosm experiment with benthic microalgae, Eggers, Eriksson, & Matthiessen, demonstrated that Shannon diversity significantly declined after a heat wave.…”
Section: Discussionsupporting
confidence: 93%
“…In recent years, a growing number of studies have focused on how phytoplankton primary productivity and species composition are influenced by increasing water temperatures, triggered by an interest in how global warming affects ecosystem processes and properties (Burgmer & Hillebrand, 2011;De Senerpont Domis, Mooij, & Huisman, 2007;Deng et al, 2014;Urrutia-Cordero et al, 2017). Resulting from experimental observations, the species-shift hypothesis was formulated (Daufresne, Lengfellner, & Sommer, 2009;Rasconi, Gall, Winter, & Kainz, 2015;Rasconi, Winter, & Kainz, 2017;Sommer, Peter, Genitsaris, & Moustaka-Gouni, 2017), which predicted that the proportion of small-sized phytoplankton species generally increases with temperature; however, its general applicability is still controversial (Winder & Sommer, 2012). Several microcosm and mesocosm studies also demonstrated that heterotrophic bacteria benefit more than eukaryotic algae from lake warming (Rasconi et al, 2015;Weisse, Gr€ oschl, & Bergkemper, 2016;Weisse, Anderson, et al, 2016;Wohlers-Z€ ollner et al, 2012).…”
mentioning
confidence: 99%
“…The present study also indicated that air and water temperatures contribute to the abundance of morphotypes in different sampling sites as evident from scatter plot analysis [58]. Similarly, these two factors had the strongest effect in driving morphotypes abundance in an aquatic system [59]. Cluster analysis indicated existence of three different clusters, and it indicated that each cluster shared different parameters with their specific lineage.…”
Section: Discussionsupporting
confidence: 67%
“…In particular, we postulated that sampling during extreme events, which are often missed in low-frequency routine monitoring programmes, reduces the calculated annual biovolume of taxa that are sensitive to disturbances and increases the biomass of other, more robust taxa that may take advantage of increased temperature and/or reduced competition in the course of disturbances. Several experimental microcosm and mesocosm studies have already demonstrated these mechanisms for dominant freshwater phytoplankton taxa (Rasconi et al, 2015(Rasconi et al, , 2017Weisse et al, 2016). Secondly, we hypothesised that the methodology of the current monitoring programmes underestimates various phytoplankton groups, namely small and fragile cells or colonies that are sensitive to fixation and/or difficult to detect with the common resolution of light microscopy (Gieskes & Kraay, 1983;Rodriguez et al, 2002).…”
Section: Introductionmentioning
confidence: 98%